Pengaruh Inflasi dan Tingkat Pengangguran terhadap Kesejahteraan Masyarakat melalui Indeks Pembangunan Manusia di Kabupaten Dompu - Deswita Deswita; Samsudin Samsudin; Firmansyah Firmansyah (AKUNTANSI 45, 2026)
This study aims to analyze the effect of inflation and the unemployment rate on community welfare, both directly and through the mediating role of the Human Development Index (HDI), among the working-age population in Dompu Regency. A quantitative approach with an explanatory design was employed, involving 97 respondents selected through purposive sampling based on the Lemeshow formula. Primary data were collected through a Likert-scale questionnaire and field observation, then analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that inflation has a significant positive effect on community welfare but not on HDI, while the unemployment rate is the most dominant determinant, exerting a large effect on both community welfare and HDI. In contrast, HDI does not significantly affect community welfare and fails to mediate the effects of either inflation or unemployment on welfare. The research model explains 76.5% of the variance in community welfare and 63.7% of the variance in HDI. These findings confirm that directly addressing employment issues should be the foremost priority in efforts to improve community welfare in Dompu Regency, rather than relying on human development achievements as an intervening pathway.